Interrelationship between skin sensitization, rhinitis, and asthma in patients with allergic rhinitis: a study of Spain and Portugal - Valero, A (2009)
OBJECTIVE: Allergic rhinitis can determine the presence and type of asthma. The main aim of this study was to evaluate the link between allergic rhinitis, asthma, and skin test sensitization in patients with allergic rhinitis. METHODS: Patients with allergic rhinitis, aged 10 to 50 years, were consecutively enrolled at different allergy centers in Spain and Portugal. All the patients underwent skin prick tests with a panel of 20 biologically standardized aeroallergens. Allergic rhinitis was classified according to etiology and the Allergic Rhinitis and its Impact on Asthma guidelines and asthma was classified according to the Global Initiative for Asthma guidelines. RESULTS: A total of 3225 patients, with a mean age of 27 years, were evaluated. House dust mites and grass and olive tree pollens were the most common aeroallergens. The mean (SD) number of positive skin tests per patient was 6.5 (4), the mean wheal size was 42.3 (28) mm2, and the mean atopy index was 6.5 (2). Forty-nine percent of the patients had concomitant asthma. Asthma severity was associated with a longer time since onset (P < .04) and allergic rhinitis severity (P < .001). Patients with concomitant asthma had a significantly higher number of aeroallergens and sensitization intensity than those without asthma (P < .001). CONCLUSIONS: In this broad population sample, the presence and type of asthma was influenced by skin sensitization and both time since onset and severity of allergic rhinitis.